Ex Vivo Ovine Model for Surgical and Microsurgical Training on Parotidectomy and Facial Nerve Reanimation: Proposal of Structured Training Program - Ghirelli, Michael; Federici, Gaia; Melchiorri, Claudio; Malagoli, Andrea; Presutti, Livio; Fernandez, Ignacio Javier (Journal of Reconstructive Microsurgery, 2020)
Introduction Facial nerve palsy has a great physical and psychological impact on patients, so the avoidance of facial nerve damage during surgery and its reanimation are important for Otolaryngologists and head and neck surgeons. The acquisition of anatomical knowledge and surgical training regarding the parotid surgery and facial nerve is mandatory, but not easy to achieve. Surgical simulation is a reliable alternative to the on-the-job learning. In the study, we tested an ex vivo animal model to obtain the basic and advanced skills of parotid gland surgery and facial nerve reconstruction/reanimation.Materials and Methods A prospective cohort study has been conducted on ovine head and neck specimen. A junior resident, a senior resident, and an expert surgeon were involved in a step-by-step preplanned dissection, divided in macroscopic and microscopic. Each procedure was recorded and evaluated by an expert surgeon following an adapted rating scale.Results A statistically significant improvement in terms of execution times and quality of the work was show in most of the surgical steps and for many quality items by the junior and senior residents, while the expert surgeon, as expected, did not show any improvement.Discussion Our ex vivo ovine model provided the trainee with close-to-real tissues in term of elastic resistance and consistency, to learn the skills requested in a head and neck surgery, on a reproducible environment. It is mandatory to have a feedback, which focuses on the quality of the work through valid and reliable assessment of technical skills. The judgment parameters should be reproducible and focused on the specific surgical procedure. Some limitations to this study are present, such as anatomical differences between ovine and human and the limited number of study participants.Conclusion This proposal of training program on the ex vivo ovine model for the acquisition of skills needed in head and neck surgery proved to be feasible, effective, repeatable, and cheap.
Keywords: surgical training; facial nerve; animal model